2017
DOI: 10.15698/mic2017.09.589
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol inhibits translation to limit growth and filamentation in C. albicans and S. cerevisiae

Abstract: Candida albicans is a polymorphic yeast where the capacity to switch between yeast and filamentous growth is critical for pathogenicity. Farnesol is a quorum-sensing sesquiterpene alcohol that, via regulation of specific signalling and transcription components, inhibits filamentous growth in Candida albicans. Here we show that farnesol also inhibits translation at the initiation step in both Candida albicans and S. cerevisiae. In contrast to fusel alcohols, that target the eukaryotic initiation factor 2B (eIF2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 61 publications
(126 reference statements)
0
17
0
2
Order By: Relevance
“…This ability of facile invasion is due to a combination of a weakening of the host's immune system and important virulence factors of C. albicans (Höfs et al 2016). Among the virulence factors of C. albicans in superficial and systemic infections is the ability to morphologically transition between yeast and hyphae forms, as well as the ability to form biofilms (Borghi et al 2016;Egbe et al 2017;Mayer et al 2013;Vila et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This ability of facile invasion is due to a combination of a weakening of the host's immune system and important virulence factors of C. albicans (Höfs et al 2016). Among the virulence factors of C. albicans in superficial and systemic infections is the ability to morphologically transition between yeast and hyphae forms, as well as the ability to form biofilms (Borghi et al 2016;Egbe et al 2017;Mayer et al 2013;Vila et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to increasing farnesol concentrations (0, 3, 30, and 300 μM), morphological transition from yeast to hyphal forms was prevented at the highest concentration[ 22 ]. When exposed to farnesol at concentrations of 1-50 μmM, a decrease in the pathogenicity of C. albicans was noted due to the inhibition of hyphae formation.…”
Section: Discussionmentioning
confidence: 99%
“…Farnesol, a first quorum sensing (QS) molecule identified in eukaryotic microorganisms (6), play an important role in an array of biological functions such as virulence, biofilm formation, and competence (7). Numerous studies have reported the effect of farnesol on C. albicans growth and pathogenesis (8-10). In C. albicans , farnesol inhibits the dimorphism (6) that prevent its establishment in different environmental conditions (11), it has antioxidant effects (12) and it inhibits transporters (13).…”
Section: Introductionmentioning
confidence: 99%